Hyperconnectivity during screen-based stories listening is associated with lower narrative comprehension in preschool children exposed to screens vs dialogic reading: An EEG study. - Rola Farah; Raya Meri; Darren S Kadis; John Hutton; Thomas DeWitt; Tzipi Horowitz-Kraus (PLoS ONE, 2019)
Objectives Dialogic reading (DR) is a shared storybook reading intervention previously shown to have a positive effect on both literacy and general language skills. The aim of this study was to examine the effect of DR compared to screen-based intervention on electrophysiological markers supporting narrative comprehension using EEG. Methods Thirty-two typically developing preschoolers, ages 4 to 6 years, were assigned to one of two intervention groups: Dialogic Reading Group (DRG, n = 16) or Screen Story Group (SSG, n = 16). We examined the effect of intervention type using behavioral assessment and a narrative comprehension task with EEG. Results The DRG showed improved vocabulary and decreased functional connectivity during the stories-listening task, whereas the SSG group showed no changes in vocabulary or connectivity. Significantly decreased network strength and transitivity and increased network efficiency were observed in the DRG following intervention. Greater network strength and transitivity at follow-up were correlated with increased vocabulary. Conclusions The results suggest the beneficial effect of DR in preschool-age children on vocabulary and EEG-bands related to attention in the ventral stream during narrative comprehension. Decreased functional connectivity may serve as a marker for language gains following reading intervention. Significance DR intervention for preschool-age children may reduce interfering connections related to attention, which is related to better narrative comprehension.